O papel do epstein barr vírus na carcinogênese oral - Ferreira, Lígia Lavezo [UNESP]; Demathé, Adriana [UNESP]; Bernabé, Daniel Galera [UNESP]; Carli, João Paulo de; Goiato, Marcelo Coelho [UNESP]; Miyahara, Glauco Issamu [UNESP] (Instituto Metodista de Ensino Superior, 2012)
Introduction: the squamous cell carcinoma (SCC) is the head and neck cancer of higher occurrence, representing about 90% of all these tumors. The SCC has several risk factors as smoking, alcohol and some oncogenic viruses, including the Epstein Barr virus (EBV). The EBV is a member of Herpesviridae family and has tropism for B lymphocytes and also for epithelial cells. Aim: the aim of this study was accomplish a review of the literature about the presence of the EBV in oral carcinomas. Conclusion: EBV is closely related to nasopharyngeal carcinoma, a SCC of high incidence in Southeast Asia, however its role in others oral SCC has not been proved.

Introdução: o carcinoma espinocelular (CEC) é o câncer de cabeça e pescoço de maior ocorrência, representando cerda de 90% de todos esses tumores. O CEC apresenta diversos fatores de risco, como fumo, álcool, e alguns vírus de potencial oncogênico, entre eles o Epstein Barr vírus (EBV) que é um membro da família Herpesviridae e apresenta um tropismo por linfócitos B e também por células epiteliais. Objetivo: realizar um levantamento na literatura da presença do EBV em carcinomas orais. Conclusão: o EBV está intimamente relacionado com carcinoma de nasofaringe, um CEC de alta ocorrência no sudeste asiático, no entanto o seu papel nos demais CEC orais ainda não foi comprovado.
The role of Epstein Barr virus in oral carcinogenesis
Keywords: Epstein-barr virus infections; Mouth neoplasms; Carcinoma; Squamous cell; Carcinoma; Infecções por vírus epstein-Barr; Neoplasias vucais; Carcinoma de células escamosas|Carcinoma